Mitochondria, complexity, and evolutionary deficit spending - Nick Lane; William Martin (2016)
Lynch and Marinov (1) challenge our findings (2) that mitochondria are essential to the prokaryote−eukaryote transition. Their paper states: “Lane and Martin introduced the cost of a gene as an argument for the impossibility of high levels of cellular/developmental complexity without a power-generating mitochondrion.” Scrutinizing bioenergetic costs, they conclude that “an energetic boost associated with the emergence of the mitochondrion was not a precondition for eukaryotic genome expansion” (1).